Detection of enterotoxin genes of Staphylococcus sp isolated from nasal cavities and hands of food handlers - Rall, V. L. M. [UNESP]; Sforcin, J. M. [UNESP]; Augustini, V. C. M. [UNESP]; Watanabe, M. T. [UNESP]; Fernandes Jr., A. [UNESP]; Rall, R.; Silva, M. G. [UNESP]; Araújo Jr., J. P. [UNESP] (Sociedade Brasileira de Microbiologia, 2010)
Food handlers, an important factor in food quality, may contain bacteria that are able to cause foodborne disease. The present study aimed to research coagulase-negative (CNS) and -positive staphylococci (CPS) in 82 food handlers, analyzing nasal and hand swabs, with identification of 62 CNS (75.6%) and 20 CPS strains (24.4%). Staphylococcal enterotoxins genes were investigated by PCR. In 20 CPS strains, 19 were positive for one or more genes. The percentage of CNS presenting genes for enterotoxins was high (46.8%). Despite of the staphylococcal species, the most common gene was sea (35.4%), followed by seh and sej (29.2%). The detection of new staphylococcal enterotoxins (SEs) genes showed a higher pathogenic potential in this genus. The presence of these gene points out the importance of CNS not only as contaminant bacteria but also as a pathogen.
Keywords: Staphylococcal enterotoxins; coagulase-negative staphylococci; S. aureus; food handler